Space management's regarding safety level at construction site / Aizat Ilman On and Wan Samsul Zamani Wan Hamdan - On, Aizat Ilman; Wan Hamdan, Wan Samsul Zamani (2018)
The purpose of this research is to identify about space management regarding the safety level at a construction site. The accident or injuries occurred on the site have also caused by the improper site space management or site layout planning due to lack of fulfil the safety level requirement. Safety officer and Contractor at construction site should recognize roughly how to improvise space management layout at construction site to avoid any safety hazards or accident occur to all workers. Safety officer also needs to control not only all the workers at construction site, but also to make an assessment of the space management layout at the construction site. The main purpose of assessment of the space management layout is to ensure site layout planning complies the safety level requirement for avoiding safety issues on site. Therefore, about 30 questionnaires had been distributed among selected safety officer and contractor at three selected existing construction sites. The data has been analysed by applying Statistical Package for the Social Sciences (SPSS) through frequency analysis. The finding on space management issues on construction sites were on improper placement of storage material due to insufficient space and crowded, which impact on difficulty of site logistics operations.